Research of the figures of primary school-age girls regarding correspondence of current typology - Рудік, Р. А.; Зубкова, Л. І. (Fashion Industry, 2023)
Research of the possibility of using the existing regulatory and technical documentation for designing clothes for girls of primary school age. In the researchuses the contact method of obtaining anthropometric information characterizing the figure of the child. An anthropological method was used to determine body types. According to the existing regulatory and technical documentation, changes in the structure of children's bodies caused by acceleration processes are not taken into account when making clothes. This leads to a violation of the conformity of the finished product and a decrease in consumer satisfaction with proportional clothing. This also indicates the need to carry out a wide study of the body structures of the children's population in order to revise the existing system of typical figures, namely, to determine the types of body structure and their quantitative characteristics. A significant inconsistency in the typological composition of the typical figures of modern girls was established, namely, only 62.3% of the modern figures of girls of primary school age are represented in the industry standard. On the basis of the analysis of modern typical figures of girls of junior school age, the percentage distribution of typical sizes in the sample was calculated and a list of typical figures presented in the current standard was established. The typological composition of the figures of primary school-aged girls was determined by the combination of leading dimensional features to ensure an increase in the level of satisfaction of this group of children with mass-produced clothes.